Latent profile analysis of depression in older adults spouse caregivers - Feng, Fuzhe; Huang, Yalong (Frontiers in Public Health, 2025)
ObjectiveWith advancing age, older adults are more likely to experience health problems and a decline in functioning, necessitating long-term care. Spouses play a crucial role in providing care for the older adults. Depression is a significant mental health issue faced by older adult’s spouses. Categorizing depression into homogeneous subgroups can unveil hidden insights.MethodsThis study utilized the Harmonized CHARLS dataset to investigate. Latent Profile Analysis (LPA) was employed to identify subgroups of older adult’s spouses who experience depression, and chi-square tests were conducted for univariate analysis. Furthermore, multiple logistic regression was utilized to analyze the associated factors.ResultsSpouse caregivers were identified and classified as Low Level Depression (50.6%), High Level Depression (20.0%), and Unstable Affective Depression (29.4%). Gender, education level, self-assessment of health, communication with children, social participation, life satisfaction, and place of residence were found to be influential factors for depression among older adults spouse caregivers. Multiple logistic regression analysis indicated that, compared to individuals with low levels of depression, those with high levels were significantly associated with gender, education level, self-assessed health status, social engagement, life satisfaction, and place of residence. Similarly, compared to individuals with low levels of depression, those classified as having an unstable affective type were significantly associated with gender, education level, self-assessed health status, and life satisfaction. Furthermore, compared to individuals with high levels of depression, those with unstable affective depression were significantly associated with gender, self-assessed health status, weekly interactions with children, and participation in social activities.ConclusionThis study revealed distinct subtypes of depression among older adults spousal caregivers, emphasizing the importance of targeted interventions in primary care. Tailored intervention strategies addressing the specific characteristics of each subtype may improve caregivers’ mental health and enhance their quality of life.